Structural Model of Self-Efficacy, Self-Regulated Learning, and Self-Determination on Mathematics Learning Achievement through Reasoning Ability - Aqil Fadhil MS; Hisyam Ihsan; Andi Syukriani (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study examines the effects of self-efficacy, self-regulated learning, and self-determination on students’ mathematics achievement through mathematical reasoning ability. A quantitative ex post facto design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 170 ninth-grade students at a state junior high school in Makassar, Indonesia, selected through cluster random sampling. Data were collected using validated questionnaires and a mathematical reasoning test. The results show that self-efficacy and self-regulated learning significantly influence mathematical reasoning ability, which in turn has a significant effect on mathematics achievement. Both variables also show indirect effects on achievement through reasoning ability. In contrast, self-determination does not have a significant effect on either mathematical reasoning or mathematics achievement. These findings indicate that mathematical reasoning plays a mediating role in linking self-efficacy and self-regulated learning factors to mathematics learning achievement.